Deformation and Gravity Change: Indicators of Isostasy, Tectonics, Volcanism, and Climate Change - Wolf, Detlef; Fernández, José (Pageoph Topical Volumes, 2007)
During the last decades, measurements of various geodynamic processes have gained ever increasing importance. Temporal variations of the deformation and gravity fields monitored by geodetic measuring techniques reflect isostatic, tectonic or volcanic processes in the earth's interior. Recordings of hydrologic or oceanographic phenomena allow conclusions on surface processes. This volume reflects the major developments during recent years in these areas of research. Most of the papers in this book were presented at the workshop on "Deformation and Gravity Change: Indicators of Isostasy, Tectonics, Volcanism and Climate Change", which took place at the Casa de los Volcanes on Lanzarote, Spain, during March 1-4, 2005. It was jointly organized and supported by the International Association of Geodesy (IAG), the Spanish Ministry of Education and Science, the Spanish Council for Scientific Research and the Cabildo Insular de Lanzarote. The workshop also served as the first meeting of the members of the IAG Working Group ICCT2 on "Dynamic Theories of Deformation and Gravity Fields".